Association of comorbid burden with clinical outcomes after transcatheter aortic valve implantation. Issue 24 (20th July 2018) - Bagur, Rodrigo; Martin, Glen Philip; Nombela-Franco, Luis; Doshi, Sagar N; George, Sudhakar; Toggweiler, Stefan; Sponga, Sandro; Cotton, James M; Khogali, Saib S; Ratib, Karim; Kinnaird, Tim; Anderson, Richard A; et al.
Abstract : Objectives: To investigate the association of the CharlsonComorbidity Index (CCI) with clinical outcomes after transcatheter aortic valve implantation (TAVI). Background: Patients undergoing TAVI have high comorbid burden; however, there is limited evidence of its impact on clinical outcomes. Methods: Data from 1887 patients from the UK, Canada, Spain, Switzerland and Italy were collected between 2007 and 2016. The association of CCI with 30-day mortality, Valve Academic Research Consortium-2 (VARC-2) composite early safety, long-term survival and length of stay (LoS) was calculated using logistic regression and Cox proportional hazard models, as a whole cohort and at a country level, through a two-stage individual participant data (IPD) random effect meta-analysis. Results: Most (60%) of patients had a CCI ≥3. A weak correlation was found between the total CCI and four different preoperative risks scores ( ρ =0.16 to 0.29), and approximately 50% of patients classed as low risk from four risk prediction models still presented with a CCI ≥3. Per-unit increases in total CCI were not associated with increased odds of 30-day mortality (OR 1.09, 95% CI 0.96 to 1.24) or VARC-2 early safety (OR 1.04, 95% CI 0.96 to 1.14) but were associated with increased hazard of long-term mortality (HR 1.10, 95% CI 1.05 to 1.16). The two-stage IPD meta-analysis indicated that CCI was not associated with LoS (HR 0.97, 95% CI 0.93 to 1.02). Conclusion: In this multicentre international study, patients undergoing TAVI had significant comorbid burden. We found a weak correlation between the CCI and well-established preoperative risks scores. The CCI had a moderate association with long-term mortality up to 5 years post-TAVI.